Triple helix conformation of botryosphaeran, a (1 -> 3;1 -> 6)-beta-D-glucan produced by Botryosphaeria rhodina MAMB-05 - Giese, Ellen C. [UNESP]; Dekker, Robert F. H.; Barbosa, Aneli M.; da Silva, Roberto [UNESP] (Elsevier B.V., 2008)
Botryosphaeran, a (1 -> 3;1 -> 6)-beta-D-glucan produced by Botryosphaeria rhodina MAMB-05, was found to be present in a triple helix conformation from helix-coil transition studies using Congo Red. The triple helix conformation was disrupted at increasing alkali concentrations. Conformational changes were also observed using phenanthrene as a fluorescent probe, and the fluorescence intensity decreased 80% in the presence of dimethyl sulfoxide. The results confirmed the triple helix conformation of botryosphaeran, an important property manifesting biological response modifying activity. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Botryosphaeran; (1 -> 3;1 -> 6)-beta-D-glucans; Botryosphaeria rhodina MAMB-05; Triple-helix conformation